Influence of exercise variation on the retention of a pacing strategy - Mauger, A.; Jones, A.; Williams, C. A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In competitions where time to completion is the measure of success, pacing strategy exerts an important influence on performance. The Theory of Teleoanticipation and the Central Governor Model, proposes that a pacing strategy is set in a feedforward manner, based on distance or duration, prior to the onset of an exercise bout. Prior experience of an exercise bout allows the construction of a pacing schema, which is utilised for subsequent, similar bouts of exercise. During exercise, distance or time remaining is judged by an `internal clock` that is located in the brain. It is proposed that this timing mechanism works in a scalar fashion, using relative rather than absolute quantities. Despite the apparent importance of the scalar clock to the maintenance of a pacing strategy, knowledge in this area is presently limited. Aims: To establish whether the introduction of an exercise bout of different distance, in the absence of distance feedback, would affect the retention of the pacing schema stored from a prior exercise bout. Furthermore, to identify whether the internal clock has an ability to calibrate to absolute distance, and whether this mechanism is disrupted by an exercise requiring a different pacing strategy. Methods: Sixteen highly-trained male cyclists were randomly split into a control (CON) or experimental group (EXP) and completed four time trials (TT) of two different distances (2x4 km and 2x6 km) in varying orders, separated by 17 minutes. The participants in the CON group completed both distances in a sequential order (i.e. half performed 4 km, 4 km, 6 km, 6 km, and the other half performed 6 km, 6 km, 4 km, 4 km). The EXP group completed both distances in a variable order (i.e. half performed 4 km, 6 km, 4 km, 6 km, and the other half performed 6 km, 4 km, 6 km, 4 km). During each TT, power output, VO2 and heart rate were recorded. Participants in both groups were asked to call out their RPE for every km they thought they had completed. Results: No significant differences were found between or within groups for completion time or PO (p > 0.05). The CON group showed a significant improvement in their estimation of distance completed in both the 4 km (24.6 ± 18.2 % vs. 8.2 ± 5.5 %) and 6 km (15.2 ± 7 % vs. 8.6 ± 3 %) distances (t7 = 2.791, t7 = 3.118, p < 0.05). No significant differences in distance estimation were observed in the EXP for either of the TT distances (p > 0.05). Conclusion: The primary finding of this study is that participants who did not receive an exercise interruption displayed a significant improvement in their judgement of distance completed, despite no improvement in completion time. This suggests that a learned pacing schema is robust and not negatively affected by subsequent pacing variation and can be retrieved when required. The internal clock shows an ability to be calibrated to absolute distance, although this does not improve performance.